Whose needs count in situations of forced displacement? Revaluing older people and addressing their exclusion from research and humanitarian programmes. (15th May 2019) - Kaga, Midori; Nakache, Delphine
Older people remain one of the most neglected, invisible, and marginalised groups among displaced persons, which is in part due to ageist stereotypes that persist and permeate the humanitarian system. Using a theoretical framework grounded in the capabilities approach, this article examines urban/protracted situations of displacement in developing countries and highlights gaps in the limited knowledge and assistance to older displaced persons that must be bridged in order to break the vicious cycle between research and policy that continue to marginalise older persons from humanitarian responses. At the heart of the issue around older peoples' exclusion and invisibility is their lack of voice in decision-making processes and their capacity to contribute to improving the programmes and policies that directly impact them. The paper thus also argues for the meaningful inclusion of older displaced persons in decision-making processes around programmes that concern them.